A standardized method for collection of human placenta samples in the age of functional magnetic resonance imaging - Victoria HJ Roberts; Jessica E Gaffney; Katherine S Lewandowski; Matthias C Schabel; Terry K Morgan; Antonio E Frias (BioTechniques)
Current methods for placental tissue collection assess a delivered organ without direct functional correlates; therefore, the four-quadrant biopsy protocol utilized by many researchers may provide reasonable representation of tissue across a large organ, and offer a snapshot for molecular analysis of the placenta. However, the recent impetus to understand the placenta in real time, and the use of functional imaging to comprehend placental biology, warrants a different sampling approach. Here we present a method to standardize placental tissue collection in a format designed to facilitate correlation of in vivo function with ex vivo assessments. Additionally, we draw comparisons to the quadrant biopsy regimen, and highlight a pathological case of placental infarction detected by in utero imaging.